Factors Analyze on the Performance of Nurses in the Implementation of Patient Safety - Ida Sukaesi (Universitas Muhammadiyah Malang, 2017)
Nurse have an important good role for safety of patients by monitoring the patients' condition to prevent the occurrence of incidents, provide health education, detect faults and near misses, and perform other tasks to solve a problem of the patients by high-quality care. The problems have been existing in ER related to the implementation of patient safety is that the patient safety has not been accomplished in accordance with the SPO and Patient Safety Guide. The purpose of this study is to analyze the factors associated with the performance of nurses in the implementation of patient safety. The research uses analytical descriptive design with cross sectional approach. The number of samples used is 23 respondents with total sampling technique . The calculation results of multiple regression analysis of patient safety knowledge factors have the most dominant influence with standardized ß coefficient of 0.678 and 0.329 meaning that it has a significant effect while the supervision does not. Optimizing the development of the individual nurse requires efforts to increase knowledge and skills in the context of patient safety; therefore, they are able to show high-quality performance.